Photo/Electrochemical Applications of Metal Sulfide/TiO2 Heterostructures. Issue 1 (21st November 2019) - Zheng, Lingxia; Teng, Feng; Ye, Xiaoying; Zheng, Huajun; Fang, Xiaosheng
Abstract: Developing efficient and affordable catalysts is of great significance for energy and environmental sustainability. Heterostructure photocatalysts exhibit a better performance than either of the parent phases as it changes the band bending at the interfaces and provides a driving force for carrier separation, thus mitigating the effects of carrier recombination and back‐reaction. Herein, the photo/electrochemical applications of a variety of metal sulfides (MS x ) (MoS2, CdS, CuS, PbS, SnS2, ZnS, Ag2 S, Bi2 S3, and In2 S3 )/TiO2 heterojunctions are summarized, including organic degradation, water splitting, and CO2 reduction conversion. First, a general introduction on each MS x material (especially bandgap structures) will be given. Then the photo/electrochemical applications based on MS x /TiO2 heterostructures are reviewed from the perspective of light harvesting ability, charge carrier separation and transportation, and surface chemical reactions. Special focus is given to CdS/TiO2 and PbS/TiO2 ‐based quantum dot sensitized solar cells. Ternary composites by taking advantages of positive synergetic effects are also well summarized. Finally, conclusions are made regarding approaches for structure design, and the authors' perspective on future architectural design and electrode construction is given. This work will make up the gap for TiO2 nanocomposites and shed light on the fabrication of more efficient MS x ‐metal oxide junctions in photo/electrochemical applications. Abstract : Structure steering of MS x /TiO2 heterojunctions in photodegradation, water splitting, and CO2 conversion are reviewed herein, mainly focusing on improved light harvesting, effective interfacial charge transfer, and affordable active sites for surface chemical reactions. Special focus is given to the quantum dot sensitized solar cells.